Infrared thermography as a non-destructive test for the inspection of reinforced concrete bridges: A review of the state of the art - Aquino Rocha, Joaquin Humberto; Vieira Póvoas Tavares, Yêda (Revista ALCONPAT, 2017)
This article aims to present the methodologies, advantages and limitations of the infrared thermography test for the inspection of reinforced concrete bridges. A systematic review of articles and academic material related to the area was carried out. This review focuses mainly on the passive application and on both laboratory and field studies. A critical approach to the information available was used in relation to its scope was used. The test is presented as a real alternative for the detection of defects in these structures, being more effective the more superficial these anomalies. Depending on the work to be done, it is necessary to contemplate some considerations to obtain better results. And it is effective in combination with other tests.